2020
DOI: 10.3892/ol.2020.12356
|View full text |Cite
|
Sign up to set email alerts
|

P4HB: A novel diagnostic and prognostic biomarker for bladder carcinoma

Abstract: Prolyl 4-hydroxylase, beta polypeptide (P4HB) protein is an endoplasmic reticulum (ER) molecular chaperone protein and has been reported to be overexpressed in multiple tumor types. However, the role of P4HB in bladder cancer (BLCA) has not yet been elucidated. The aim of the present study was to investigate the prognostic value of P4HB and the association between clinicopathological characteristics and P4HB in BLCA. P4HB expression levels were assessed through The Cancer Genome Atlas (TCGA) and Gene Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…Due to the significance of UPR in tumors, many researchers have paid more attention to UPR related biomarkers. It has been reported that OTUB1, P4HB, and EHMT2 could regulate the malignant phenotype of bladder cancer cells via the ERS related URP pathway ( Cui et al, 2015 ; Wang et al, 2020 ; Zhang et al, 2021c ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significance of UPR in tumors, many researchers have paid more attention to UPR related biomarkers. It has been reported that OTUB1, P4HB, and EHMT2 could regulate the malignant phenotype of bladder cancer cells via the ERS related URP pathway ( Cui et al, 2015 ; Wang et al, 2020 ; Zhang et al, 2021c ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PPIB, a peptidylpropyl isomerase, participated in colorectal cancer progression and chemoresistance [49]. Studies have also suggested that P4HB may extensively regulate tumor progression and prognosis of patients with cancer [50][51][52][53][54], including BRCA [55,56]. In BRCA, TMED9 may affect cancer progression and prognosis by interacting with these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy-related gene prolyl 4-hydroxylae, beta polypeptide (P4HB) has been validated as a promising diagnosis and prognosis biomarker in kidney renal clear cell carcinoma [21] and bladder cancer [22]. Besides, P4HB contributes to cell proliferation, migration or invasion in gastric cancer [23], breast cancer [24] and colon cancer [25] through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%